TAL effectors: tools for DNA Targeting - Jankele, Radek (Oxford University Press, 2014)
Xanthomonas phytopathogenic bacteria produce unique transcription activator-like effector (TALE) proteins that recognize and activate specific plant promoters through a set of tandem repeats. A unique TALE-DNA-binding code uses two polymorphic amino acids in each repeat to mediate recognition of specific nucleotides. The order of repeats determines effector’s specificity toward the cognate nucleotide sequence of the sense DNA strand. Artificially designed TALE-DNA-binding domains fused to nuclease or activation and repressor domains provide an outstanding toolbox for targeted gene editing and gene regulation in research, biotechnology and gene therapy. Gene editing with custom-designed TALE nucleases (TALENs) extends the repertoire of targeted genome modifications across a broad spectrum of organisms ranging from plants and insect to mammals.